Breaking Corn Yield Barriers: A Cropping Systems Approach - G. R. Balboa; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2016)
During 2015, four corn research trials were conducted in dryland and irrigated environments. Two trials were at Scandia, KS and two were in Topeka, KS. The objective of these trials was to study the contribution of different farming management approaches for developing efficient and high-yielding corn production systems. Treatment layout consisted of five combinations: common practices (CP), comprehensive fertilization (CF), production intensity (PI), ecological intensification (CF + PI), and advanced plus (AD). Under dryland and irrigation scenarios, EI and AD treatments presented the highest yields relative to the other combinations. Under irrigation, absolute yield gap was larger in both locations as compared to the dryland scenario. The EI and AP treatments produced better yields than all other treatments at all sites and water conditions.
Keywords: corn; yield gaps; cropping system